Housing cultural studies: A memoir of Stuart Hall, Richard Hoggart and Terence Hawkes - Hartley, John (2015)
© The Author(s) 2014. Three globally significant figures in cultural studies died in 2014. They were Terence Hawkes (13 May 1932–16 January 2014), Stuart Hall (3 February 1932–10 February 2014) and Richard Hoggart (24 September 1918–10 April 2014). I miss them all. That personal feeling motivates what follows. But there’s a public aspect to it too. Not only did I watch and admire these three people building cultural studies; I know the buildings they built it in. Suddenly those buildings feel empty, not facing the future but confined to their times, ceasing to ‘speak’ as they silently await sufficient neglect and dilapidation to justify the new-generation wrecking ball of ‘creative destruction’ to open up the space for something new that has already forgotten them.